Integrated methodology for production related risk management of vehicle electronics (IMPROVE) - Geis, Stefan Rafael (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Universität Karlsruhe (TH), Institut für Rechneranwendung in Planung und Konstruktion (RPK), 2006)
This scientific work is designated to provide an innovative and integrated conceptional approach to improve the assembly quality of automotive electronics. This is achieved by the reduction and elimination of production related risks of automotive electronics and the implementation of a sustainable solution process. The focus is the development and implementation of an integrated technical risk management approach for automotive electronics throughout the vehicle life cycle and the vehicle production planning process.